Visualizing Values: A Content Analysis to Conceptualize Value Congruent Video Messages Used in Agricultural Communications - Laura Morgan Fischer; Kelsi Opat; Kayla Jennings; Courtney Meyers (Journal of Applied Communications, 2021)
Visual messaging is becoming the new avenue to connect with consumers. The majority of the American public is not connected with agriculture and often questions procedures, practices, and tactics within the industry. Practitioners and researchers have suggested value congruent messages, a type of emotional appeal, may increase attention to agricultural messages. However, limited research has been conducted to define and investigate value congruent messages in agricultural communications. The purpose of this study was to describe the presented messages in videos used in one agricultural advocacy effort, CommonGround’s “Nothing to Fear Here” campaign. This content analysis described the video’s message content and use of value congruent messages. Schwartz Theory of Basic Human Values (2012) was used to identify the values present in each video within the campaign. The values of benevolence, security, self-direction, universalism, and hedonism were common values displayed in the campaign. Message sensation value was calculated, and it was found the videos had moderate levels of emotional arousal. The primary characters in the videos were mothers, farmers, and children. More research should be conducted to explore how the value congruent messages and message sensation value interact to increase a receiver’s level of attitude change after viewing the message.
Keywords: message sensation value; value congruent messages; framing; message appeals; videos